Challenges faced by rights discourse - Pérez Luño, Antonio Enrique (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Throughout its evolution, every theory usually faces certain challenges that prove its vitality. The discourse of rights, as a theoretical conception aimed at its explanation and foundation, is not exempt from the permanent task aimed at responding to these challenges. This essay analyzes the risks that are considered most decisive and pressing for the discourse of rights. To this end, three current challenges to the theory of rights are studied and three responses to them are suggested. Eleaticism, particularism and posthumanism are considered the main challenges facing reflection on rights today. The response to these attitudes is constituted by historicism, universalism and humanism.
Keywords: human rights; eleaticism; particularism; posthumanism; historicism; universalism; humanism